Optimal dosage ranges of various exercise types for enhancing timed up and go performance in Parkinson’s disease patients: a systematic review and Bayesian network meta-analysis - Yuan, Yuan; Wang, JunYu; Wang, GuoTuan; Wang, Tao; Zhang, HaoYang; Fu, XueYing; Wu, LiHua; Chen, XiaoTian; Xia, Rui; Zhang, Lin; Lin, Shu-Cheng; Yang, Yong (Frontiers in Aging Neuroscience, 2024)
Study analysis: Data analysis was conducted using R software with the MBNMA package. Effect sizes of outcome indicators were expressed as mean deviation (MD) and 95% confidence intervals (95% CrI). The risk of bias in the network was evaluated independently by two reviewers using ROB2.: A total of 73 studies involving 3354 PD patients. The text discusses dose-response relationships in improving TUG performance among PD patients across various exercise types. Notably, Aquatic (AQE), Mix Exercise (Mul_C), Sensory Exercise (SE), and Resistance Training (RT) demonstrate effective dose ranges, with AQE optimal at 1500 METs-min/week (MD: -8.359, 95% CI: -1.398 to -2.648), Mul_C at 1000 METs-min/week (MD: -4.551, 95% CI: -8.083 to -0.946), SE at 1200 METs-min/week (MD: -5.145, 95% CI: -9.643 to -0.472), and RT at 610 METs-min/week (MD: -2.187, 95% CI: -3.161 to -1.278), respectively. However, no effective doses are found for Aerobic Exercise (AE), Balance Gait Training (BGT), Dance, and Treadmill Training (TT). Mind-body exercise (MBE)shows promise with an effective range of 130 to 750 METs-min/week and an optimal dose of 750 METs-min/week (MD: -2.822, 95% CI: -4.604 to -0.996). According to the GRADE system, the included studies' overall quality of the evidence was identified moderate level.This study identifies specific exercise modalities and dosages that significantly enhance TUG performance in PD patients. AQE emerges as the most effective modality, with an optimal dosage of 1500 METs-min/week. MBE shows significant benefits at lower dosages, catering to patients with varying exercise capacities. RT exhibits a nuanced "U-shaped" dose-response relationship, suggesting an optimal range balancing efficacy and the risk of overtraining. These findings advocate for tailored exercise programs in PD management, emphasizing personalized prescriptions to maximize outcomes.